Trends in the initial management of vestibular schwannoma in the United States. (October 2019) - Leon, Janet; Trifiletti, Daniel M.; Waddle, Mark R.; Vallow, Laura; Ko, Stephen; May, Byron; Tzou, Katherine; Ruiz-Garcia, Henry; Lundy, Larry; Chaichana, Kaisorn; Vibhute, Prasanna; Peterson, Jennifer L.
Highlights: This national analysis examines the care of patients with vestibular schwannoma. 28, 446 patients with vestibular schwannoma were evaluated. Age, location, payer, and facility type are factors that influence initial treatment. Abstract: Introduction: Vestibular schwannomas are benign tumors of the 8th cranial nerve. Initial treatment options include active surveillance, surgery, and/or radiation therapy. We analyzed the United States National Cancer Database (NCDB) for patients with vestibular schwannomas and evaluated the initial management trends after diagnosis. Methods: We queried the NCDB for patients with vestibular schwannomas, excluding patients who did not have schwannomas of the vestibulocochlear nerve. Categorical and continuous variables were analyzed, and multivariate Cox regression analyses were performed to investigate for predictors of initial local therapy at diagnosis. All statistical analyses were performed using commercially available software (SPSS, Version 22; SPSS Inc., Chicago, IL). Results: A total of 28, 446 patients met the inclusion criteria. In this cohort, 7351 (25.8%) underwent observation, 12, 362 (43.5%) underwent surgical resection, 7785 (27.4%) underwent SRS, 824 (2.9%) underwent EBRT, and 124 (0.4%) underwent RT NOS. On multivariate analysis, younger age, increased distance to treating facility, Charlson/Deyo score of 1, primary payer insurance, facility location and facility type (academic or cancer center) ( p < 0.001) were all factors that predicted patients undergoing initial definitive treatment. Conclusion: Age, distance to treating facility, Charlson/Deyo score, primary payer, facility location, and facility type are factors that influence initial treatment for patients with vestibular schwannoma. Clinical stratification systems are needed to identify which patients would benefit most from initial local therapy versus active surveillance.